Employees' job satisfaction as a predictor of clients' satisfation on the products and services provided by banks in the City of San Fernando, La Union - Gamata, Roy A. (Laoag City : [s.n.], 2018)
The study determined the level of job satisfaction of government and private bank employees along the following job factors: work content, pay and promotion, working conditions, working group, supervision, and personality job fit. It also determined the level of satisfaction of bank clients on the products and services of the government and private banks. The study covered two hundred seventy nine (279) employees and one hundred thirty five (135) clients of twenty five (25) private banks and two (2) government banks in the City of San Fernando, La Union. The study employed the descriptive-correlation research design. Two sets of questionnaires were used to gather data on the satisfaction of bank employees and clients. Weighted mean, t-test, Pearson Product Moment Correlation and Coefficient of Determination were used to analyze and interpret the data.
Bibliography: pages 92-95.
CHED-La Union
Keywords: Job satisfaction